Obtain Cucurbitacin from Ecballium elaterium and Cucurbita pepo and Converting into a Pharmaceutical Form - Derya Duran (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2019)
The squirting cucumber plant is widely used in the treatment of sinusitis,rheumatism, and hepatitis.It is reported that the liquid obtained from fruitsis widely used in the treatment of sinusitis among people, especially inTurkey. The active components of Nigella sativa seeds are shown to beeffective in inflammatory diseases caused by histamine. In this study, it wasaimed to create a spray form by extracting Ecballium elaterium andCucurbita pepo plants, which are easily found in almost every region ofTurkey, mixing them with black cumin oil which is used widely andtraditionally, and using inactive ingredients. Firstly, the amounts ofcucurbitacin D, I, B, E from Ecballium elaterium were determined by HPLCand validation of cucurbitacin active substance analytical method wasperformed. Physicochemical properties of the nasal spray including pH,osmolality, specific gravity, and viscosity values were determined. Skinirritation, sensitization, and cytotoxicity tests were performed on the finalproduct. The total amount of cucurbitacin D, I, B, E in squirting cucumberwas found to be about 4% of the fruit juice. The proportion of thesesubstances was also examined in squash juice and was found to be 0.033%for the respective amount. Skin irritation, sensitization, and cytotoxicitytests were performed in the obtained product and no adverse effects wereobserved. In addition, physicochemical parameters of the spray, such aspH, osmolality, specific gravity, and viscosity were measured. Results werefound as 6.179, 630 mOsmol/L, 55.4 Mpa/s and 1,080 g/cm3 at ph 25 ºC,respectively.